Naujesni tarmių fonetinės transkripcijos rašmenys - Skirmantas, Petras; Girdenis, Aleksas (Kalbotyra, 1998)
The paper deals with a modernised system of phonetic transcription and a set of computer fonts for both Lithuanian dialectology and phonetics. This proposal may be treated as an attempt to restore and develop the former Lithuanian phonetic alphabet, created by G. Gerullis (in collaboration with E. Sievers) in the early thirties, and almost entirely forgotten (at least - inconceivably simplified) after the War.